Magical practice in the Latin West: papers from the international conference held at the University of Zaragoza, 30 Sept.-1 Oct. 2005 - Gordon, Richard L.; Marco Simón, Francisco (Religions in the Graeco-Roman world, 2010)
Preliminary Material /Marco Simón and R.L Gordon -- Introduction /Richard Gordon and Francisco Marco Simón -- Chapter One. Magus And Its Cognates In Classical Latin /James B. Rives -- Chapter Two. Magic In The Roman Historians /Matthew W. Dickie -- Chapter Three. Heretical Texts And Maleficium In The Codex Theodosianus (Cth. 16.5.34) /María Victoria Escribano Paño -- Chapter Four. The Defixiones From The Sanctuary Of Isis And Mater Magna In Mainz /Jürgen Blänsdorf -- Chapter Five. Religion And Magic At Rome: The Fountain Of Anna Perenna /Marina Piranomonte -- Chapter Six. The Texts From The Fons Annae Perennae /Jürgen Blänsdorf -- Chapter Seven. Cursing A Thief In Iberia And Britain /Roger Tomlin -- Chapter Eight. Prayers For Justice, East And West: New Finds And Publications Since 1990 /Henk S. Versnel -- Chapter Nine. How Does Magical Language Work? The Spells And Formulae Of The Latin Defixionum Tabellae /Amina Kropp -- Chapter Ten. Inversion, Adversion And Perversion As Strategies In Latin Curse-Tablets /Christopher A. Faraone and Amina Kropp -- Chapter Eleven. Execrating The Roman Power: Three Defixiones From Emporiae (Ampurias) /Francisco Marco Simón -- Chapter Twelve. Nails For The Dead: A Polysemic Account Of An Ancient Funerary Practice /Silvia Alfayé Villa -- Chapter Thirteen. Magic At Sea: Amulets For Navigation /Sabino Perea Yébenes -- Chapter Fourteen. A Prayer For Blessings On Three Ritual Objects Discovered At Chartres-Autricum (France/Eure-Et Loir) /Richard Gordon , Dominique Joly and William Van Andringa -- Chapter Fifteen. Mithraism And Magic /Jaime Alvar Ezquerra -- Chapter Sixteen. A Visigothic Charm From Asturias And The Classical Tradition Of Phylacteries Against Hail /Francisco Javier Fernández Nieto -- Chapter Seventeen. Between Orthodox Belief And ‘Superstition’ In Visigothic Hispania /Isabel Velázquez Soriano -- Chapter Eighteen. Celtic Loricae And Ancient Magical Charms /Pierre-Yves Lambert -- General Index /Marco Simón and R.L Gordon -- Select Index Of Texts And Documents Cited /Marco Simón and R.L Gordon -- Index Of Latin Words /Marco Simón and R.L Gordon -- Select Index Of Greek Words /Marco Simón and R.L Gordon.